The Combination and Development of Chinese and Western Classical Decorative Patterns for the Contemporary Design - Hongsu, Wang; Aromdee , Korakot; Vanitwatthananuwat, Chaiyot (Journal of Roi Kaensarn Academi, 2024)
This research will study and explore the innovative expression of Chinese and Western decorative patterns in contemporary design, explore new styles and application fields, enrich and expand the expression techniques and creativity of decorative pattern art, and also enhance and promote Communication and understanding between different cultures. The objectives of this study are：(1) To study the components of the combination and development of Chinese and western classical decorative patterns for the contemporary design.(2) To compare and analyze the combination and development of Chinese and western classical decorative patterns for the contemporary design. (3) To design and development of Chinese and western for new patterns，that is applied to contemporary. The research was a mixed methodology research. Population was art design teachers in universities under Liaoning Province, totaling 2134 people, sample size 327. The sample size was determined by Krejcie and Morgan’s Table (1970) was obtained by stratified random sampling method, sample size was 327. The instruments used for data collection were semi-structured interview form, five-point rating scale questionnaires and focus group discussion form. The response rate of questionnaires was 100%. Statistics used for data analysis included frequency, percentage, mean, standard deviation, exploratory factor analysis, and content analysis. The research findings were revealed that (1) the combination and development of Chinese and western classic decorative patterns for the contemporary design consisted of 5 components as follow, color contains 18 variables, innovation design contains 10 variables, culture contained 10 variables, pattern contains 6 variables, artistic contains 4 variables. These variables will help provide information for the survey. To compare and analyze the combination and development of Chinese and western classical decorative patterns for the contemporary design. And in the field of application，decorative pattern art provide new evidence and support for the social value and cultural inheritance.